PELATIHAN METODE AKTIF UNTUK PENINGKATAN KUALITAS PEMBELAJARAN DI SEKOLAH MENENGAH PERTAMA (SMP) PULAU PANJANG TIMUR - Juni Mahanis; Nurhayati; Enik Nurfaizah; Usvim Varadilla; Dina Liana; Mukhammad (Universitas 'Aisyiyah Surakarta, 2025)
This training aimed to improve the quality of learning in Junior High Schools (Sekolah Menengah Pertama, SMP) in Pulau Panjang Timur through active learning method training for teachers. The quality of education in remote areas such as Pulau Panjang Timur often faces challenges such as limited access to innovative teaching methods and low student engagement in the learning process. Therefore, training in active learning methods serves as a solution to enhance student participation, improve understanding of subject matter, and strengthen teachers' teaching skills. This research employed a qualitative approach using a case study method involving observations and in-depth interviews with teachers and students who participated in the training. The results show that the active learning method training successfully improved teacher competence. Prior to the training, the teachers’ understanding of digital media was only at 58% (categorized as